GESTÃO POR COMPETÊNCIAS: AVALIAÇÃO E PROPOSTA DE MELHORIAS NO PROGRAMA DE UM ÓRGÃO DO JUDICIÁRIO ELEITORAL - Soares, Adriana Petersen Saraiva (2020)
The greater participation and demand of society for more efficient and higher quality services, as well as the need for organizations to build strategies to achieve this purpose, contributed to the emergence of Competency-based Management in the public se